Extended Protective Shield Under Table to Reduce Operator Radiation Dose in Percutaneous Coronary Procedures: The EXTRA-RAD Study. (February 2019) - Sciahbasi, Alessandro; Sarandrea, Alessandro; Rigattieri, Stefano; Patrizi, Roberto; Cera, Maria; Di Russo, Cristian; Zezza, Luigi; Fedele, Silvio; Ferraiuolo, Giuseppe
Abstract : Background: Different tools and devices are effective to reduce operator radiation exposure at thorax level during percutaneous coronary procedures, but the operator radiation dose received at pelvic region still remains high. Our aim was to evaluate the efficacy of under-the-table adjunctive shields to reduce operator radiation exposure during percutaneous coronary procedures Methods and Results: The EXTRA-RAD study (Extended Protective Shield Under Table to Reduce Operator Radiation Dose in Percutaneous Coronary Procedures) is a prospective, single-center, randomized study. Patients who underwent transradial coronary procedures were randomized into 2 groups: group 1 (standard arrangement) and group 2 (adjunctive anti-rx shield under the angiographic table). In group 2, a further randomization was performed to compare 2 different under-the-table shields (a small curtain and a drape). A total of 205 procedures (122 diagnostic coronary angiographies and 83 percutaneous coronary interventions) performed in 157 patients by 4 different operators were included without significant differences in clinical and procedural characteristics between groups. The use of adjunctive shields was associated with lower radiation dose compared with no shield at pelvic region (42 µSv [14–98] in group 1, 13 µSv [5–27] in group 2; P <0.0001) and also at thorax level (4 µSv [1–13] in group 1, 2 µSv [1–4] in group 2; P =0.001). The reduction in dose was observed in all the operators. No significant differences were observed in pelvic dose using the 2 different shields ( P =0.183). Conclusions: The use of adjunctive anti-rx shields under the angiographic table during transradial coronary procedures is associated with a significant lower radiation dose to operators at pelvic and thorax level. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT03259126. Abstract : Supplemental Digital Content is available in the text.